VARIATIONS IN SENSE OF PLACE ACROSS IMMIGRANT STATUS AND GENDER: RELATIONSHIP TO AIR QUALITY PERCEPTIONS AMONGST WOMEN IN HAMILTON, ONTARIO, CANADA - Gallina, Melissa (My University, 2014)
In the first paper, sense of place (SoP) is used to evaluate immigrant experiences in three small to medium-sized Canadian cites: Hamilton, ON; Saskatoon, SK; and, Charlottetown, PEI. First, quantitative analysis is used to compare SoP amongst immigrant and Canadian-born respondents in the three cities. Ordered logistic regression determined four significant predictors of SoP: income; age; neighbourhood length of residence and, city of residence. Despite an observed difference in evaluations of SoP between immigrants and Canadian-born individuals, regression analysis did not identify immigrant status as a significant predictor of SoP.
The second paper employs a mixed-methods strategy to examine individual perceptions of air quality and sense of place amongst Canadian-born and immigrant women in Northeast Hamilton. Furthermore, the study aims to determine the influence of sense of place on local environmental perceptions. Qualitative focus group discussions suggest that Canadian-born women may be more aware, knowledgeable and concerned about large-scale air quality issues; however, the tension between economic and environmental needs hinders their sense of control. Quantitative survey results suggest that Canadian-born residents have a higher absolute value of sense of place than immigrants. Bringing together the qualitative and quantitative data suggests that sense of place may inform environmental perceptions.
Keywords: Sense of Place; Environmental Perceptions; Immigrants; Hamilton; Canada; Women; Human Geography; Human Geography